ANALYSIS OF POLYMORPHISMS OF RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM AND RELATION TO VASOPRESSORS IN ESSENTIAL SYSTEMIC HYPERTENSION WITH THE LEFT VENTRICLE HYPERTROPHY IN DAGESTAN REPUBLIC - M. Z. Saidov; S. N. Mammaev; A. A. Abdullaev; T. B. Arapkhanova; G. R. Israilova (Российский кардиологический журнал)
Aim. To assess the prevalences of genotypes and alleles polymorphisms of reninangiotensin-aldosterone  system,  and  β2-adrenoreceptors,  and  to  evaluate  the results  in regard   to  vasopressor  levels  in blood  serum  in essential   systemic hypertension  (ESH) with the  left ventricle hypertrophy  (LVH)  and  with none,  in Dagestan  Republic population.Material and methods. To the assessment, 98 patients included with the diagnosis “essential systemic hypertension  with or none LVH”. Genotypes  were assessed, of polymorphism A1166C gene AGTR1 and polymorphism Arg16Gly gene ADRB2. The testing of the polymorphisms was performed  with allele-specific polymerase  chain reaction.  Level of angiotensin  (At) II, endothelin (et) 1-21 and aldosterone (AS) in blood serum was measured by the hard-phase IeA. Level of ACe was measured by enzymatic method. Statistics was done with the software statistica (version 6.0) and “Biostat 4.03”.Results.  In EAH  patients   with LVH  the  prevalence   of  Arg/Arg polymorphism Arg16Gly gene  ADRB2  was  lower than  in control.  In EAH  with no LVH  there  is significant decline  of AC genotype  prevalences of polymorphism  A1166C gene AGTR1 and genotype  Arg/Arg polymorphism Arg16Gly gene ADRB2. Level of EТ1-21  and АТ II in the group of EAH with no LVH patients was significantly higher than in controls. Level of AT II in EAH with LVH was significantly higher than none LVH group. Increase of the levels of these mediators of AH was followed by a decline of AS level in the groups  of patients  comparing  to controls. In EAH group with LVH significant increase of et 1-21 was associated with the carriage of As polymorphism A1166C gene AGTR1, and genotypes АА and СС of the same polymorphism were associated with the decrease of levels of EТ1-21. In EAH with no LVH a significant decrease of At  II  level was found in the  carriers  of AA  and  AC genotypes of polymorphism A1166C  gene   AGTR1.  Also, the  association   was  found  of  all  genotypes  of polymorphism Arg16Gly gene ADRB2  with the decrease of АТ II.Conclusion. In Dagestan  population, in EAH with and with no LVH, most significant are  genotypes  AA,  AC and  CC  of  polymorphism  A1166C gene   AGTR1,  and genotypes Arg/Arg, Arg/Gly, Gly/Gly and alleles Arg and Gly polymorphism Arg16Gly gene ADRB2. Pathogenic  significance of the mentioned  polymorphisms is emphasized by the presence of polymorphism ET1-12, АТ II, Аs in blood serum.